2019
DOI: 10.1007/s00382-019-05044-0
|View full text |Cite
|
Sign up to set email alerts
|

Advancing global storm surge modelling using the new ERA5 climate reanalysis

Abstract: This study examines the implications of recent advances in global climate modelling for simulating storm surges. Following the ERA-Interim (0.75° × 0.75°) global climate reanalysis, in 2018 the European Centre for Medium-range Weather Forecasts released its successor, the ERA5 (0.25° × 0.25°) reanalysis. Using the Global Tide and Surge Model, we analyse eight historical storm surge events driven by tropical-and extra-tropical cyclones. For these events we extract wind fields from the two reanalysis datasets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 59 publications
(68 reference statements)
3
65
0
2
Order By: Relevance
“…ERA5 data were released in 2019 and are freely available in Google Earth Engine and the Copernicus Climate Data Store. Studies have shown ERA5 to have satisfactory performance in accurately modeling storm surges ( 141 ), Canadian prairie climate ( 142 ), and global discharge reanalysis ( 143 ) compared to previous generations and other models. ERA5 monthly aggregated precipitation and temperature values were summarized annually and seasonally over the study domain.…”
Section: Methodsmentioning
confidence: 99%
“…ERA5 data were released in 2019 and are freely available in Google Earth Engine and the Copernicus Climate Data Store. Studies have shown ERA5 to have satisfactory performance in accurately modeling storm surges ( 141 ), Canadian prairie climate ( 142 ), and global discharge reanalysis ( 143 ) compared to previous generations and other models. ERA5 monthly aggregated precipitation and temperature values were summarized annually and seasonally over the study domain.…”
Section: Methodsmentioning
confidence: 99%
“…While data with such a resolution performs reasonably for extratropical storms (Dullaart et al, 2019), it strongly underestimates the intensity of tropical cyclones (Schenkel and Hart, 2012) and associated storm surges (Bloemendaal et al, 2017;Muis et al, 2019). In 2019, the European Centre for Medium-Range Weather Forecasts (ECWMF) released the ERA5 climate reanalysis dataset.…”
Section: Introductionmentioning
confidence: 99%
“…The ERA5 gridded reanalysis data set was used to select the climatological forcing factors, including the pressure at mean sea level (SLP) and the corresponding gradients (GRDslp), the meridional and zonal wind components at 10 m (Uwind and Vwind, respectively), the temperature in 850 hPa (850T), the geopotential heights in 700 hPa (700Z), as well as the total precipitation (TP). The ERA5 reanalysis data set has a spatial resolution of 0.25 × 0.25° and a one‐hour temporal resolution, which is available from 1 January 1979 to present (Dullaart et al., 2020). To link the ERA5 reanalysis data set with the SSL records, the meteorological variables were averaged over the neighboring window of size 3 × 3 centered at each tidal gauging station to eliminate the bias caused by the spatially heterogeneous surface (see Text of the supplementary material for sensitivity analysis of grid sizes).…”
Section: Extreme Storm Surge Observations and Climatological Forcing mentioning
confidence: 99%